Simulated Microgravity Induces Microvolt T Wave Alternans - Grenon, S. Marlene (Ann Noninvasive Electrocardiol, 2005)
Background: There are numerous anecdotal reports of ventricular arrhythmias during spaceflight; however, it is not known whether spaceflight or microgravity systematically increases the risk of cardiac dysrhythmias. Microvolt T wave alternans (MTWA) testing compares favorably with other noninvasive risk stratifiers and invasive electrophysiological testing in patients as a predictor of sudden cardiac death, ventricular tachycardia, and ventricular fibrillation. We hypothesized that simulated microgravity leads to an increase in MTWA. Methods: Twenty‐four healthy male subjects underwent 9 to 16 days of head‐down tilt bed rest (HDTB). MTWA was measured before and after the bed rest period during bicycle exercise stress. For the purposes of this study, we defined MTWA outcome to be positive if sustained MTWA was present with an onset heart rate ≤125 bpm. During various phases of HDTB, the following were also performed: daily 24‐hour urine collections, serum electrolytes and catecholamines, and cardiovascular system identification (measure of autonomic function). Results: Before HDTB, 17% of the subjects were MTWA positive [95%CI: (0.6%, 37%)]; after HDTB, 42% of the subjects were MTWA positive [95%CI: (23%, 63%)] (P = 0.03). The subjects who were MTWA positive after HDTB compared with MTWA negative subjects had an increased versus decreased sympathetic responsiveness (P = 0.03) and serum norepinephrine levels (P = 0.05), and a trend toward higher potassium excretion (P = 0.06) after bed rest compared to baseline. Conclusions: HDTB leads to an increase in MTWA, providing the first evidence that simulated microgravity has a measurable effect on electrical repolarization processes. Possible contributing factors include loss in potassium and changes in sympathetic function.